2021
DOI: 10.1016/j.bjpt.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance difference on the six-minute walk test on tracks of 20 and 30 meters for patients with chronic obstructive pulmonary disease: validity and reliability

Abstract: Background: Functional capacity assessment is important in patients with chronic obstructive pulmonary disease (COPD). It can be performed by the six-minute walk test (6MWT) on a 30meter track. However, such space is not always available in clinical settings. Objectives: To compare the performance between the 6MWT on a 30-(6MWT 30 ) and 20-meter (6MWT 20 ) track; to evaluate the validity and reliability of the 6MWT 30 and the 6MWT 20 ; and to determine for which patients track length has the greatest impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
2
16
2
Order By: Relevance
“…Overall, healthy adults did not walk further on a 30m course when compared to either a 15m course (p = .06) or a 20m course (p = .08). Our results are in contrast with previously reported scholars who found course length to affect distance walked [1,[9][10][11] . Although our study is inconsistent with previously reported literature, our study is one of the few that used healthy adults.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Overall, healthy adults did not walk further on a 30m course when compared to either a 15m course (p = .06) or a 20m course (p = .08). Our results are in contrast with previously reported scholars who found course length to affect distance walked [1,[9][10][11] . Although our study is inconsistent with previously reported literature, our study is one of the few that used healthy adults.…”
Section: Discussioncontrasting
confidence: 99%
“…In our pilot study, course length did not affect distance walked in healthy adults aged 18-30. These results are inconsistent with previous studies which outlined course length affected distance ambulated [1,[9][10][11]. One explanation for this inconsistency is our sample size of age 18-30, healthy adults.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study found significant difference of 6MWD between a 20-m and a 30-m walkway in that walking distance on 20-m walkway is shorter than on a 30-m by an average of 22.03 m and had 4.88 more turns. These results correspond to the study of Klein SR, et al [10]. They found that, in COPD patients, 6MWD with 30-m walkway was significantly longer than 20-m walkway (mean difference in 22.1 m) [10].…”
Section: Discussionsupporting
confidence: 89%